Pendampingan Untuk Kreasi Sungai Larangan Di Desa Bilebante, Kecamatan Pringgarata, Lombok Tengah - Akhmad Saufi; Agusdin; Alamsyah; Diswandi (Jurnal Pengabdian Magister Pendidikan IPA, 2023)
Bilebante is a tourism village which is rich with nature-based attractions and is one of the accredited-sustainable tourism villages in Lombok. One of the potential nature-based attractions in this village is the river. Hence, the preventive actions toward the negative environmental impacts of tourist activities should be implemented in early stage of its development. This community service is organised in order to empower the local people in Bilebante with nature-related tourism knowledge and skills for they can manage the river as a tourist attraction and as well as a conservation area. The local people’s enthusiasm to participate in this empowerment program indicate their strong willingness to develope a nature-based tourism attraction within the village and as well as the success of this community service program.